2023
DOI: 10.1108/jocm-05-2022-0146
|View full text |Cite
|
Sign up to set email alerts
|

SME internationalisation: past, present and future trends

Abstract: PurposeSmall- and medium-sized enterprises (SMEs) generally make a crucial contribution to local and national economies. As the market has become increasingly globalised over the past two decades, SMEs often feel the need and/or push to internationalise their business activities. It is in this need that several barriers and challenges are perceived by SMEs, since these companies generally have different characteristics and resources compared to large multinational enterprises (MNEs). Accordingly, given that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…D. Sarasvathy, 2001) in extending the opportunity-based view of traditional SMEs’ internationalization by investigating the role of AMC, GM, and CI in IOI and IOE. Fernandes et al (2023) argued that intrinsic characteristics of SMEs’ managers and SMES’ resources and capabilities are two fundamental theoretical approaches to explaining SMEs internationalization. This study concluded that AMCs, GM, and CI are essential for IOI and IOE among Chinese internationalized traditional SMEs.…”
Section: Discussionmentioning
confidence: 99%
“…D. Sarasvathy, 2001) in extending the opportunity-based view of traditional SMEs’ internationalization by investigating the role of AMC, GM, and CI in IOI and IOE. Fernandes et al (2023) argued that intrinsic characteristics of SMEs’ managers and SMES’ resources and capabilities are two fundamental theoretical approaches to explaining SMEs internationalization. This study concluded that AMCs, GM, and CI are essential for IOI and IOE among Chinese internationalized traditional SMEs.…”
Section: Discussionmentioning
confidence: 99%
“…Small and medium-sized enterprises (SMEs) are considered a central part of global economies, contributing to innovation practises, internationalisation activities, economic development and sustainability transitions (Fernandes et al. , 2023; Jansson et al.…”
Section: Introductionmentioning
confidence: 99%
“…This configures an important gap in the literature considering not only the importance of SMEs for global economies, but also the distinct features of SMEs and large business that the business model research tends to focus on (Cosenz and Bivona, 2021;Foss and Saebi, 2018;Spieth et al, 2014;Zott et al, 2011). This paucity of research gains further significance considering that SMEs often undergo business model transformation and business model innovation to implement innovation practises (Balakrishnan and Das, 2020;Hu and Hughes, 2020;Liao et al, 2019), entrepreneurial practises (Asemokha et al, 2019;Cucculelli and Bettinelli, 2015), internationalisation practises (Dabi c et al, 2020;Fernandes et al, 2023;Sadeghi et al, 2023), digital practises (Bahoo et al, 2023;Bouncken et al, 2021;Bouwman et al, 2019;Ghezzi and Cavallo, 2020) and sustainable practises (Chaudhuri et al, 2022;Klewitz and Hansen, 2014;Vrontis et al, 2021) that are key to their performance. The research on business models of SMEs tends to focus on specific aspects, such as circular business models (Ferasso et al, 2020;Geissdoerfer et al, 2020), sustainable business models (Ferreira et al, 2022), sustainable entrepreneurship , sharing economy business models (Soltysova and Modrak, 2020) and business model experimentation towards digital transformation (Bouwman et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation